Sosialisasi LKPD Dengan Model Discovery Learning Melalui Aplikasi Docfly - Wati, Retno Isna (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Education serves as the fundamental foundation for building an empowered society. In an era of rapid global change, the provision of education is no longer the exclusive responsibility of formal educational institutions alone. Close collaboration among educational institutions, students, parents, and the wider community is essential to achieve optimal learning outcomes. One crucial instrument in supporting high-quality learning processes is the Student Worksheet (LKPD). However, many education students still lack an understanding of the significance of LKPD.Analysis results indicate that the success of introducing and implementing LKPD at Unwidha Campus inspires continuous progress in designing and developing student-centered, dynamic, and contemporary learning. The involvement of participants, positive outcomes, and enthusiasm establish a solid foundation for exploring the innovative potential of LKPD and applying it to enhance the quality of education in the future. Overall, this community service activity is not an end goal but an initial step that holds promise for further developing innovative learning concepts and making a positive impact on education at Unwidha Campus.